Estimation Method for Emission of Road Transport - Torok Adam (European Regional Science Association (ERSA), 2006)
It is a well-known that the growth of GDP induces the growth of motorization. Motorization has developed so dramatically that the air, soil, water pollutions are considerable to the amounts of air, soil and water of Earth. Some of the pollutants affect on local or regional scale while others affect on global scale. There is the natural, non-antropogeneous greenhouse gas emission developed before the human activity that has been essential for life on Earth. Without it the average world temperature would be -20C. [1] Sustainable development is a development where the pace of technical development, the satiation of increasing supply, raw materials and resources of Earth are poised so that the rate of living and opportunities of the next generations need not to be worse. So global warming caused by the antropogeneous and non-antropogeneous CO2 can be estimated. The measured data is from the non-antropogenous source, but prediction can be done. To have the best result I have made a Best Fit Analize. The prediction should be parabolic because when the CO2 concentration grows smog or cloud arises that blocks sunlight from Earth, the only source of heat. The growing CO2 concentration part of the parabola can be approximated by linear trend. The other part of the emissions caused by the motorization is local or regional. Theoretically one solution could be to stop motorised transportation. Transportation cannot be replaced because it is the part of the production chain. Societies are horizontally and vertically differential. People live in different places and do different things for living. The manpower, the stock, the semi-finished and finished products must be transported. The importance of the transportation sector is indicated by the sector production which is 10% of the GDP of the European Union and more than 10 million people are working in this sector. One of the most emphasized goals of the transport policy of the European Union is sustainable mobility. For this reason transportation systems must be developed and standardized, the effectiveness of transportation service must be increased, while the environmental pollution must be decreased or prevented. This is a task for engineers and operators as well. People who would like to make rational decisions, make an optimization, choosing the maximum utility and benefit. Theoretically, all benefits and costs should be accounted in the analysis. Externalities should be internalised and indicated in the cost of transportation according to the EU guideline ,,Users should pay the bill". Some of the external costs can simply be added to the average costs but some of them need a totally different aspect and pricing method, the marginal costs based pricing method. The more realistic pricing method we want the more externalities should be included to the marginal costs based pricing method. Some of them can be calculated and monetized, some of them can be estimated, and some of them cannot be expressed in monetary terms. The environmental external effects of transport cover a wide range of different impacts, including for example noise, local/regional air pollution and climate change. Transport infrastructure projects often affect local and regional air pollution. Emissions from road traffic are good examples of a complex system with an output that cannot be completely measured. It is natural to analyze the emissions from a sample of vehicles under different driving conditions and other conditions (temperature, fuel content, road gradients, etc.) and to try to create an emission model for the traffic. Depending on what data are collected about the traffic the model may be more or less detailed and complex. Traffic data are not collected in the same way and with the same level of detail in every country and this is a problem if a model is meant to be used for calculations in many countries or for comparisons between them. The EURO standards based on the ECE-R15 driving cycle: [3] Each vehicle category has its own limits. The vehicle flow can be divided into groups by EURO standards and vehicle categories with its pollutant limits. Being aware of the vehicle numbers in each category multiplied with the limit they can be summarised. Now the pollutants can be calculated from the given vehicle flow and the given distance. [4]
Keywords: 330